2016
DOI: 10.1088/1748-0221/11/07/p07007
|View full text |Cite
|
Sign up to set email alerts
|

Design, construction and commissioning of the Digital Hadron Calorimeter—DHCAL

Abstract: Abstract.A novel hadron calorimeter is being developed for future lepton colliding beam detectors. The calorimeter is optimized for the application of Particle Flow Algorithms (PFAs) to the measurement of hadronic jets and features a very finely segmented readout with 1 × 1 cm 2 cells. The active media of the calorimeter are Resistive Plate Chambers (RPCs) with a digital, i.e. one-bit, readout. To first order the energy of incident particles in this calorimeter is reconstructed as being proportional to the num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…These former results, obtained with small detector prototypes, suggested that RP-WELL detectors are promising for applications that require cost-effective solutions for large-area coverage. For example, the Digital, or Semi-Digital Hadron Calorimeter ((S)DHCAL) [9,10], foreseen for the SiD experiment in the future international linear collider (ILC) [11], the overall instrumented area will be as large as ∼4000 m 2 . Another application could be photon detection for large-area UV-RICH detectors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…These former results, obtained with small detector prototypes, suggested that RP-WELL detectors are promising for applications that require cost-effective solutions for large-area coverage. For example, the Digital, or Semi-Digital Hadron Calorimeter ((S)DHCAL) [9,10], foreseen for the SiD experiment in the future international linear collider (ILC) [11], the overall instrumented area will be as large as ∼4000 m 2 . Another application could be photon detection for large-area UV-RICH detectors [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a 1x1 cm 2 pad is economically affordable with respect to 3x3 cm 2 scintillator tiles. The CALICE collaboration has been studying the performance of digital [85] and semi-digital [86] hadronic calorimeters. Besides having a high granularity, gaseous detectors have the advantage to be radiation hard, leading to simple calibration procedures.…”
Section: Micro-pattern Gaseous Detector-based Samplingmentioning
confidence: 99%
“…Two gaseous HCAL prototypes, the digital HCAL (DHCAL) [15] and the semi-digital HCAL (SDHCAL) [6] have been built. Both have a 1 m 2 active area of Glass Resistive Plate Chambers (GRPC) read by 1 cm 2 copper pads interleaved with stainless steel absorber plates.…”
Section: Hcal Prototypesmentioning
confidence: 99%